VD_FINDINFO Arrêt / 2014 / 14 vom 19. Dezember 2013 - VD Tribunal cantonal (2013)
AC, REMISE DE LA PRESTATION, RESTITUTIONEN GÉNÉRAL, PRINCIPE DE LA BONNE FOI | 95 al. 1 LACI, 25 al. 1 LPGA, 4 al. 1 OPGA